PERANCANGAN TONGKAT BANTU INOVATIF UNTUK TUNANETRA DENGAN MEMANFAATKAN TEKNOLOGI SENSOR GYROSCOPE, GPS DAN ULTRASONIK - Agung Pambudi; Muhammad Diego Leonardo (Universitas Alma Ata, 2023)
The eyes are vital human sensory organs that react to light. One of the functions of the eyes is to record the state or surrounding conditions, to know the object. Then, cones on the retina allow conscious light perception and vision, such as color differentiation and depth perception. The purpose of the research was to develop stick-based technology gyroscope sensors, GPS, and ultrasonic-based microcontrollers. The development of this tool aimed at helping blind people to detect objects around them so that blind people could walk well. The approach in this development utilized the Research and Development (R&D) method, and the testing used the Alpha method. The test results showed that all tools could function properly and could be implemented in the field.